Effect of Intellectual Capital on Return on Assets of Insurance Firms in Nigeria (Global Journal of Management and Business Research, 2016)
Intellectual capital represents the efforts of workers towards the growth of an organization. The inability of firms to measure and quantify intellectual capital has posed fundamental problems overtime in the value measurement of firms. The purpose of this study is to evaluate the effect of IC in the value creation of insurance firms in Nigeria using their ROA. Expost facto research design was adopted in the selection of data. Primary and secondary data were employed. The target population consisted of 150 workers in the 3 strategic departments of human resources, accounts and marketing of 18 insurance companies using the purposive sampling technique. 150 questionnaires were distributed and a response rate of 74% was recorded. Face validity, content validity and pilot test were used to validate the instruments. The Cronbach's Alpha reliability test gave a result of (r=0.806) and (r=0.800) respectively. Regression was used for data analyses at 5% level of significance.
Keywords: intellectual capital; financial performance; insurance firms; value added